Batik in the Perspective of Recognition Search: Its Achievements and Preservation - Iswahyudi Iswahyudi (Budapest International Research and Critics University, 2021)
The existence of batik which now seems to be an Indonesian national identity has a long history. When talking about batik, people will automatically refer to the state of Indonesia. However, until now people still continue to seek recognition of it, besides of course that is no less important is the need for efforts for its development and preservation. In this case, the Indonesian people need to be careful in responding to globalization in its most tangible form, for example prioritizing the importance of nationalism and also in its implementation being realized in the form of cultural resilience because it is recognized as a cultural capital that is considered capable of being a filter for globalization. Batik on the one hand is a cultural resilience that deserves to be offered as cultural capital or in a minimal form as a reflection of ideological fragments that play a role in providing identification or identity to the Indonesian people.